A importância dos estudos de usuários na formação do arquivista - Glaucia Aparecida Vaz (2015)
This study aims to demonstrate, according the archivists attributions, their professional background and practices, how the Users Studies approach can contribute to improve those practices. It discusses about the archivists, their professional roles and how they have been changed in the society context. Thenceforth it addresses the many fields of professional performances, more concentrated currently in the public administration. It seeks to understand questions related to the files access, using the world and Brazilian laws, about the information access rights. Understanding these laws it makes possible to recognize how that access is made in Brazil. Its shown a historical background about the users studies inside archiving area, from the files opening process to a consolidated law access, relating that evolution from the first studies in the 60s to the current thoughts in the area. To evaluate how important are the users studies classes a questionnaire was developed to evaluate them inside each course program. Interviews were made with teachers and coordinators from eight archiving undergraduate courses in the country, to understand some historical questions about file access, new technologies impact and the Information Access Law, the use and files users on three phases, state of the art of the discussion about users studies in archiving area, and practices to guarantee access and promote file recognition as a construction space of collective memory and citizenship promoting. At the end it is possible to realize that the current scenario is friendly to consolidate actions and practices, but also to open an investigation agenda turned to the files users specifications.